Francis Cooray and Khoo Salma Nasution, redoubtable reformer: the life and times of Cheah Cheang Lim. Penang: Areca Books, 2015. 225+xvii pages. ISBN 978-967-5719-20-2 - Hossain, Ishtiaq (IIUM Press, 2015)
A biography may be defined as “our non-fictional output devoted to recording and interpreting real lives” (Hamilton 1). Biographies generally range along a continuum from scholarly to popular to super-pop. Redoubtable Reformer: The Life and Times of Cheah Cheang Lim is a biography with a difference. It does not fall into any of the categories of biography just mentioned. It is neither a scholarly nor a popular biography. Rather it is the story of, as the title suggests,of an awesome reformer living in Federated Malaya.